Conn’s Syndrome Due to Adrenal Adenoma - Rasyid, Haerani; Bakri, Syakib; Kasim, Hasyim; Hidayat, Andi Rahmat; Syarif, Syarif; Azis, Abd (UI Scholars Hub, 2019)
Conn’s syndrome is characterized by an increase in aldosterone level causes sodium retention and an increase in urine excretion of potassium. This syndrome is characterized by trias hypokalemia, hypertension, and metabolic alkalosis. This article discussed a case report of a patient with uncontrolled hypertension with neuromuscular symptoms caused by recurrent hypokalemia. After an evaluation of the imaging test, we found a left adrenal tumor then we performed unilateral adrenalectomy surgery. Histopathology examination from the excised tumor revealed the adrenal adenoma. After unilateral adrenalectomy, the patient showed clinical and laboratory improvement.